The geomorphic control on the initiation and propagation of the Mt. di Vezzi landslides (Ischia Island, Italy) occurred on 30th April 2006 - Ascione, Alessandra; Cinque, Aldo; Franza, Annamaria; Romano, Paola (Italian journal of engineering geology and environment, 2007)
This paper summarises the first results of a geomorphological study we carried out in the area struck by the 30th April 2006 landslides, in Ischia island. This study aimed at the documentation of the landslide traces, and at providing new evidences on the role played by the pre-existing landforms in the location of the source areas, in landslide propagation and motion, and in the distribution of localized and distal accumulation. This was done through field surveys (started soon after the events), and by analyses of aerial photographs, topographic maps and of DTM. Besides the reconstruction of the main stages of landscape evolution of the Ischia sector including the area struck by the landslides, a detailed landscape analysis of the latter area was carried out. This allowed classification of the study area in terms of dip values and land systems, and identification of minor geomorphic elements which compose each unit. Afterwards, the relationships among the features of the single units/elements and landslide initiation, propagation and accumulation were investigated. Although the Ischia case provided a small population of phenomena, it they may be considered as a representative study case for the pyroclastic earth slides which have been affecting the Campania region in the last decennia. The integration of the collected evidences with those deriving from the pre-existing record of cases highlights, above others, the important control exerted by steep elements breaking the hillslopes not only on initiation, but also on propagation of the landslides. The recognised role of subvertical elements suggests the crucial importance of their detection in landsliding susceptibility assessment. As a consequence, in cases where the presence of such elements is not proved but only inferred, the susceptibility threshold slope angle should be prudentially lowered.